Comprehensive comparison of the applicability of internally ribbed and microfin tubes for TORC systems. (1st May 2022) - Wang, Dabiao; Lu, Hang; Li, Lanlan; Fu, Shilin; Dai, Xiaoye; Shi, Lin
Highlights: Heat transfer enhanced tube selection criteria are evaluated. Heat transfer of supercritical R134a was experimentally investigated in a MFT and an IRT. Heat transfer coefficient, buoyancy effect and pressure loss were compared. A new enhanced tube criterion is proposed. Abstract: TORC (Trans-critical Organic Rankine Cycle) systems are a promising thermal conversion technology. However, the heat transfer deterioration with the supercritical organic working fluid can affect the system safety. Heat transfer enhanced tubes (HTET) increase the heat transfer coefficient which limits the heat transfer deterioration and improves TORC system safety and economy. However, the heat transfer enhancement in the various types of tubes has not been well quantified for equivalent conditions with contradictory conclusions affecting existing heat transfer enhancement prediction criteria. Therefore, the present study presents experimental comparisons of the heat transfer of a supercritical organic working fluid (R134a) in two different types of enhanced tubes (an internally ribbed tube and a micro-finned tube) to provide reliable experimental data to solve this contradiction. A total of 14, 100 experimental data points were obtained. The results compare the heat transfer enhancement, the restriction of the buoyancy induced heat transfer deterioration and the pressure loss factor of the tubes. The experimental results are then used to evaluate the accuracy and limitations of the existing criteria. Then, a more general tube selection criterion is presented for TORC system enhanced tube selection.